Calibration Strategies for Detecting Macroscale Patterns in NEON Atmospheric Carbon Isotope Observations. Issue 3 (26th March 2021) - Fiorella, Richard P.; Good, Stephen P.; Allen, Scott T.; Guo, Jessica S.; Still, Christopher J.; Noone, David C.; Anderegg, William R. L.; Florian, Christopher R.; Luo, Hongyan; Pingintha‐Durden, Natchaya; Bowen, Gabriel J.
Abstract: Carbon fluxes in terrestrial ecosystems and their response to environmental change are a major source of uncertainty in the modern carbon cycle. The National Ecological Observatory Network (NEON) presents the opportunity to merge eddy covariance (EC)‐derived fluxes with CO2 isotope ratio measurements to gain insights into carbon cycle processes. Collected continuously and consistently across >40 sites, NEON EC and isotope data facilitate novel integrative analyses. However, currently provisioned atmospheric isotope data are uncalibrated, greatly limiting ability to perform cross‐site analyses. Here, we present two approaches to calibrating NEON CO2 isotope ratios, along with an R package to calibrate NEON data. We find that calibrating CO2 isotopologues independently yields a lower δ 13 C bias (<0.05‰) and higher precision (<0.40‰) than directly correcting δ 13 C with linear regression (bias: <0.11‰, precision: 0.42‰), but with slightly higher error and lower precision in calibrated CO2 mole fraction. The magnitude of the corrections to δ 13 C and CO2 mole fractions vary substantially by site, underscoring the need for users to apply a consistent calibration framework to data in the NEON archive. Post‐calibration data sets show that site mean annual δ 13 C correlates negatively with precipitation, temperature, and aridity, but positively with elevation. Forested and agricultural ecosystems exhibit larger gradients in CO2 and δ 13 C than other sites, particularly during the summer and at night. The overview and analysis tools developed here will facilitate cross‐site analysis using NEON data, provide a model for other continental‐scale observational networks, and enable new advances leveraging the isotope ratios of specific carbon fluxes. Plain Language Summary: The magnitude and variability in the exchange of carbon between ecosystems and the atmosphere is a major source of uncertainty in carbon cycle models. These uncertainties have motivated substantial effort to measure these fluxes. Most observational methods provide an estimate of net carbon exchange, and efforts to break the net flux into its constituents requires a model, which without further constraints risks compounding observational uncertainties. Variations in the ratio of heavy‐to‐light carbon isotopes, 13 C/ 12 C, arise from photosynthetic responses to environmental conditions, and create a natural tracer to evaluate ecosystem fluxes. The NEON collects measurements of carbon isotope ratios of atmospheric carbon dioxide and plants and represents the largest network of consistently collected carbon isotope data associated with eddy covariance measurements to date. However, the accuracy of NEON's atmospheric carbon dioxide isotope ratios could be improved by using reference gas measurements to reduce bias and drift in these measurements. We develop and evaluate two correction methods and analyze continental‐scale patterns in the corrected atmospheric carbon dioxide isotope data. Further, we make these tools available as an R package to enable further cross‐site analyses using NEON's carbon isotope data. Key Points: Carbon isotope ratios record ecosystem assimilation and respiration processes We present methods and tools for calibrating and drift‐correcting National Ecological Observatory Network CO2 isotope measurements, which enables cross‐site analyses CO2 isotope ratios vary with site precipitation, temperature, aridity, elevation, and ecosystem structure and composition